Role of Intestinal Microbiota and its Virulence Factors in Pathogenesis of Inflammatory Bowel Disease (Medico Legal Update, 2021)
Inflammatory bowel disease (IBD) is a chronic relapsing unexplained etiological condition and microbiotahave been suggested to influence its etiology and pathogenesis. Ulcerative colitis (UC) and Crohn’s disease(CD) are the two main categories of this disease. The present study examined the fifty fecal samples obtainedfrom IBD patients and control. The bacterial isolates were identified by culture, microscope examination,biochemical test, and Vitek 2 compact system.Results showed that IBD patients havedifferent percentages ofProteobacteria (54.5%), Actinobacteria (1.6%), and Firmicutes (43.8%) when identified. They encompassed17 genera that involve 121 bacterial isolates. The corresponding percentages in control were 49%, 0%and 51%, respectively, with four genera and 68 bacterial isolates. The bacterial isolates of IBD patientsand control are assessed for some virulence factors, which included biofilm formation and production ofphospholipase and hemolysin, as well as antibiotic susceptibility. In IBD patients, evaluation of biofilmformation revealed that 20.6% of isolates were high-producing, 69.4% was moderate producing and10%non-biofilm producing. The corresponding percentages in control were 1%, 62% and 37%, respectively.The bacterial isolates showed different abilities in producing phospholipase. In samples of patients, 20.5%of isolates showed large activity, 44% moderate activity and 35.5% negative activity. For control samples,most of the isolates were non-producer of phospholipase (66%), while large and moderate enzyme activityaccounted for 4.5% and 29.5%, respectively. The hemolysin enzyme activity was determined as 35% ofisolates with high activity, 40% with moderate activity and 25% without activity. These percentages incontrol isolates were 25%, 35% and 40%, respectively. Imipenem was the most effective antibiotic againstgram-positive and gram-negative bacteria of the patient isolates with the resistance of 27% and 24%respectively, while the less effective antibiotics was cefixime with resistance of 95% and 88%, respectively.In the control isolates, the imipenem was also the most effective against bacteria with a resistance of 15%.The less effective antibiotics for gram-positive isolates was erythromycin with resistance of 43%and forgram-negative isolates, it was tetracycline was (45%).